What is the effectiveness of early palliative care integration on quality of life and symptom management in women with advanced gynecologic cancer? : A Systematic Review - Amanda Ezra Natasya Napitupulu; Jenary Immanuel Surbakti (The Indonesian Journal of General Medicine, 2026)
Introduction: Advanced gynecologic cancers are associated with significant symptom burden and impaired quality of life (QoL). While early palliative care integration has demonstrated benefits in other oncology populations, its effectiveness specifically in women with advanced gynecologic malignancies remains uncertain. This systematic review aimed to evaluate the effectiveness of early palliative care integration on QoL and symptom management in women with advanced gynecologic cancer. Methods: A systematic review was conducted following PRISMA guidelines. We included randomized controlled trials, etc examining early palliative care (initiated within 8 weeks of advanced cancer diagnosis or concurrently with active treatment) in adult women with stage III/IV or recurrent gynecologic cancers. Studies were required to report QoL, symptom management, or healthcare utilization outcomes. Data were extracted on study characteristics, interventions, and outcomes. Results: Thirty-five studies met inclusion criteria, encompassing diverse designs and populations (sample sizes 23–8,297). Ovarian cancer was most commonly studied. QoL findings were mixed: while several smaller studies reported significant improvements across FACT-G domains (p<0.05) [6,19,32], the largest RCTs in recurrent ovarian cancer failed to demonstrate significant overall QoL improvements [1,2]. A meta-analysis of four RCTs found non-significant pooled QoL effects (SMD=0.26; 95% CI -0.29–0.80) [4]. Symptom management showed more consistent benefits, particularly for acute symptom relief [8] and psychological symptoms [6]. Healthcare utilization outcomes demonstrated the most robust improvements, including reduced aggressive end-of-life care [9], increased hospice enrollment [10,11], and cost-effectiveness [17]. However, persistent underutilization (referral rates <50%) [13,14] and racial disparities [13,15] were identified. Conclusion: Early palliative care integration in advanced gynecologic cancer consistently improves healthcare utilization outcomes and shows benefits for psychological symptoms, but QoL improvements remain inconsistent across well-controlled trials. System-level interventions and standardized referral protocols may optimize real-world effectiveness. Further research should address implementation barriers and disparities.